The controversial nature of the Weissella genus: technological and functional aspects versus whole genome analysis-based pathogenic potential for their application in food and health - Abriouel, Hikmate; Lerma, Leyre Lavilla; Casado Muñoz, María del Carmen; Montoro, Beatriz Pérez; Kabisch, Jan; Pichner, Rohtraud; Cho, Gyu-Sung; Neve, Horst; Fusco, Vincenzina; Franz, Charles M. A. P.; Gálvez, Antonio; Benomar, Nabil (Frontiers in Microbiology, 2015)
Despite the use of several Weissella strains for biotechnological and probiotic purposes, certain species of this genus were found to act as opportunistic pathogens, while strains of W. ceti were recognized to be pathogenic for farmed rainbow trout. Herein, we investigated the pathogenic potential of weissellas based on in silico analyses of the 13 whole genome sequences available to date in the NCBI database. Our screening allowed us to find several virulence determinants such as collagen adhesins, aggregation substances, mucus-binding proteins and hemolysins in some species. Moreover, we detected several antibiotic resistance-encoding genes, whose presence could increase the potential pathogenicity of some strains, but should not be regarded as an excluding trait for beneficial weissellas,as long as these genes are not present on mobile genetic elements. Thus, selection of weissellas intended to be used as starters or for biotechnological or probiotic purposes should be investigated regarding their safety aspects on a strain to strain basis, preferably also by genome sequencing, since nucleotide sequence heterogeneity in virulence and antibiotic resistance genes makes PCR-based screeningunreliable for safety assessments. In this sense, the application of W. confusa and W. cibaria strains as starter cultures or as probiotics should be approached with caution, by carefully selecting strains that lack pathogenic potential.